PETROPHYSICAL AND SEDIMENTOLOGICAL CHARACTERIZATION OF THE APTIAN SHU'AIBA (LOWER QAMCHUQA) FORMATION RESERVOIR AT THE KHABBAZ OILFIELD, NORTHERN IRAQ. (October 2016) - Qader, F.; Al‐Qayim, B.
Abstract : The Aptian Shu'aiba Formation is a shallow‐marine carbonate which occurs in the subsurface of central and southern Iraq and in other parts of the Arabian Plate including Oman, the UAE and Saudi Arabia. An equivalent unit is exposed at outcrop in northern Iraq where it is known as the lower part of the Qamchuqa Formation. For this study, core, cuttings and well log data from six wells in the Khabbaz oilfield (20 km SW of Kirkuk) were used to investigate the reservoir properties of the Shu'aiba Formation. The formation is 180–195 m thick at Khabbaz field and the reservoir section can be divided into three lithological units: an upper unit (A, 8–15 m thick) consisting of partly dolomitized marly limestones; a middle unit (B, 52–56 m thick) which is composed of vuggy dolomitic limestone and dolostone; and a lower unit (C, >110 m thick) which consists of shale‐rich and dolomitic limestones. Limestone microfacies include shelfal bioclastic wackestones, Orbitolina bioclastic packstones, Orbitolina grainstones, and pelagic bioclastic wackestones. Dolomite fabrics show little variation and are dominated by coarse crystalline planar‐e types. Most matrix porosity is associated with intercrystalline pores in medium‐crystalline (100–50 µm) planar‐e dolostone. Fracturing of variable intensity has resulted in a flow type which is dominated by fracture flow superimposed on matrix flow.